A case of relapsing polychondritis initially presenting with bronchial chondritis. Issue 6 (November 2014) - Nakazato, Yoko; Mizoguchi, Fumitaka; Kohsaka, Hitoshi; Miyasaka, Nobuyuki
Abstract A 51-year-old woman presented with one-month history of fever, productive cough, dyspnea, hoarseness and polyarthritis. Computed tomography (CT) depicted diffuse bronchotracheal stenosis, which deteriorated in exhalation. Three-dimensional CT revealed airway stenosis from the trachea to the lobar bronchi. We made a diagnosis of relapsing polychondritis (RP). Administration of high-dose glucocorticoid and oral cyclophosphamide resolved the symptoms and the bronchial stenosis. It was noteworthy that all features presented were bronchial chondritis and polyarthritis. RP should be considered when patients have polyarthritis with respiratory symptoms. The dynamic expiratory CT and three-dimensional image reconstructions are useful for detecting and following up bronchotracheal involvement.